The subject of desire : Petrarchan poetics and the female voice in Louise Labé - Baker, Deborah Lesko (Purdue studies in Romance literatures ;, 1996)
The French Renaissance poet Louise Labe is one of the most striking and influential women writers of early modern Europe. In her broad-ranging volume of prose and poetic works (1555), Labe transforms the position of woman in Renaissance discourse from an object to a subject of erotic and artistic desire and privileges the notion of desire itself as a central issue for literary and psychic exploration. Deborah Lesko Baker presents the dramatic creation and evolution of female subjectivity in Labe as a passionate quest for internal selfhood made possible through both authentic self-expression and interaction with others. In so doing she analyzes how the development of the female subject coincides with an ongoing interrogation of the inherited models of the Petrarchan lyric tradition.